Sustainable Water and Wastewater Processing - Galanakis, Charis M.; Agrafioti, Evita (Elsevier, 2019)
Sustainable Water and Wastewater Processing covers the 12 most current topics in the field of sustainable water processing, with emphasis given to water as a resource (quality, supply, distribution, and aquifer recharge). Topics covered include emerging sustainable technologies for potable and wastewater treatment, water reuse and recycling, advanced membrane processes, desalination technologies, integrated and hybrid technologies, process modeling, advanced oxidative and catalytic processes, environmentally, economically and socially sustainable technology for water treatment, industrial water treatment, reuse and recovery of materials, and emerging nanotechnology and biotechnology for water processing. Responding to the goals of sustainability requires the maximum utilization of all water resources, water processing with restricted energy costs and reduced greenhouse gas production. Following these trends, this book covers all the important aspects of sustainable water processing and support.